2004
DOI: 10.1645/ge-253r
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of Cryptosporidium Oocysts by Caenorhabditis elegans

Abstract: Cryptosporidium parvum has been associated with outbreaks of human illness by consumption of contaminated water, fresh fruits, and vegetables. Free-living nematodes may play a role in pathogen transmission in the environment. Caenorhabditis elegans is a free-living soil nematode that has been extensively studied and serves as a good model to study possible transmission of C. parvum oocysts that may come into contact with produce before harvest. The objective of this study was to determine whether C. elegans co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…Insects, rotifers, and free-living nematodes could also play a role in the dissemination of oocysts, a phenomenon that has been described for Cryptosporidium (67,74,75,90,179) and other food-borne pathogens. The nematode Caenorhabditis elegans can ingest and excrete infectious bacteria (23,98,99) as well as Cryptosporidium parvum oocysts.…”
Section: Life Cyclementioning
confidence: 98%
See 1 more Smart Citation
“…Insects, rotifers, and free-living nematodes could also play a role in the dissemination of oocysts, a phenomenon that has been described for Cryptosporidium (67,74,75,90,179) and other food-borne pathogens. The nematode Caenorhabditis elegans can ingest and excrete infectious bacteria (23,98,99) as well as Cryptosporidium parvum oocysts.…”
Section: Life Cyclementioning
confidence: 98%
“…Although the oocysts of Cyclospora are larger and may not be ingested by C. elegans, other, larger species of free-living nematodes could have a significant role in Cyclospora oocyst dissemination. Therefore, the role of free-living nematodes and other mechanical vectors in the contamination of produce and other food crops needs to be examined further (90).…”
Section: Life Cyclementioning
confidence: 99%
“…Caenorhabditis elegans has been shown to ingest oocysts and excrete both intact oocysts and empty oocysts (Huamanchay et al 2004). King et al (2005) observed variation in oocyst FITC staining which they concluded could be a result of partial digestion of the oocyst wall due to predation of oocysts in raw water samples.…”
Section: B I O T I C a N T A G O N I S Mmentioning
confidence: 99%
“…In France, working with the French Association of Medical Parasitologists (ANOFEL), Guyot et (24,56). Canada geese and seagulls are occasionally mechanic carriers of human-pathogenic Cryptosporidium spp.…”
Section: Genotyping and Molecular Epidemiologymentioning
confidence: 99%